Antimicrobial Activity of Scabiosa Olivieri Extract and Its Effect on TNF-α and IL-1 Expression in Human Peripheral Blood Cells (PBMCs) - Anahita Alipoor Birgani; Nasrin Sartipnia; Seyed Mohammad Mahdi Hamdi; Mohammad Naghzadeh; Javad Arasteh (Fasa University of Medical Sciences, 2019)
Background & Objectives: Infectious diseases caused by bacteria and fungi have affected billions of people worldwide. Throughout human history, infectious diseases have been the leading cause of death and disability. Infectious diseases today account for one-third of all deaths in the world. The general objective of this study was to investigate the antimicrobial activity of Scabiosa Olivieri on gram-positive, gram-negative bacteria and fungi, as well as to study its anti-inflammatory properties by investigating the factors of human IL-1 and TNF-α, which ultimately led to the introduction of an antimicrobial agent and new anti-inflammatory drugs with a natural and inexpensive source. Materials & Methods: First, the extract of the plant was prepared by maceration. Then, the antimicrobial properties of this extract on E. coli, Staphylococcus aureus, and Candida albicans were investigated by MIC. Also, the effect of this extract on the expression of IL-1 and TNFα in human peripheral blood mononuclear cells was evaluated by ELISA. Results: Scabiosa Olivieri's extract significantly showed anti-inflammatory properties and has antimicrobial activity against Escherichia coli and a mild antimicrobial activity against Staphylococcus aureus. But the antifungal property was not observed. Conclusion: It seems that Scabiosa Olivieri's extract can be used as an anti-inflammatory and antimicrobial agent. However, the effects of its use in the in vivo environment and the chemical analysis of its constituent compounds require further research.